Introduction to networks companion guide - Cisco Networking Academy (Indianapolis : Cisco Press, 2013)
Introduction to Networks Companion Guide is the official supplemental textbook for the Introduction to Networks course in the Cisco® Networking Academy® CCNA® Routing and Switching curriculum